PENERAPAN PENGENDALIAN KUALITAS DENGAN MENGGUNAKAN METODE FMEA DAN LTA PADA LEVER ASSY PARKING BRAKE (Inaque : Journal of Industrial and Quality Engineering, 2023)
PT. KLM is a company engaged in the four-wheeled vehicle handbrake assembly manufacturing industry. The company assembles a handbrake into a complete product, which is then usually sent according to how many orders have been ordered to the company from consumers who ordered the handbrake. At PT. KLM had several production failures on one model of the lever assembly parking brake. This, of course, will have an impact on the production process in the company and loss of trust for consumers. PT. KLM wants a solution to be able to identify existing problems using the Failure Mode and Effect Analysis (FMEA) method which is intended to eliminate failures and seek solutions to the causes of production failures by setting priorities based on the Risk Priority Number (RPN) value for each failure. As for Logic Tree Analysis (LTA) to categorize events that cause production failures. Based on the results of the completion of the FMEA method, there are 10 potential causes that fall into the category of 90% of the cumulative percentage which are then categorized using the LTA method. The 10 biggest potential causes that can be identified in the use of the LTA method are such as bend in the lever according to the Standar, the Press result is less than the Standar, the Pressresult is not according to the Standar, the stopper pin does not enter, the length of the ReleaseButton that comes out is not according to the Standar.